Development and Preservation of Culinary History of Nasi Bogana in Pawon Bogana Keraton Kacirebonan - Nindita, Shafira; Wulan, Saptarining; Nahdlah, Zayyini (Institut Pariwisata Trisakti, 2019)
Nasi bogana is one of the typical culinary in Cirebon area. This culinary can be found in almost every palace in Cirebon. This cuisine is usually served during salvation or other celebrations. The Kacirebonan Palace is one of the palaces that still maintain the tradition and culture of nasi bogana. One of the efforts made by the Kacirebonan Palace was to establish a restaurant called Pawon Bogana. In the Pawon Bogana restaurant, nasi bogana is used as a mainstay menu. However, the bogana rice in the Pawon Bogana restaurant has experienced development and headway. The purpose of this study was to find out the complete history of bogana rice, the culinary development at this time when viewed from the quality and uniqueness of food and the development of bogana rice so that the culinary becomes more sustainable and awake. This study uses a qualitative method. Data sources used are sources, events and documents. Data collection techniques used are interviews, observation, documentation and questionnaires. Data analysis techniques used are data analysis that is carried out interactively and takes place continuously since data collection in the field and continues until data collection is completed. The results of the study show that Bogana Rice is one of the typical cuisines in the Cirebon area. This cuisine is usually served during salvation or other celebratory events. This culinary is used as a means of charity and is shared with others. In addition, another meaning of bogana rice is the expression of gratitude to Allah SWT. The development of bogana rice when viewed from the quality and uniqueness of food is growing and continues to innovate so that people can continue to taste the culinary. The development of bogana rice has now been carried out by the Kacirebonan Palace and continues to be carried out so that bogana rice becomes more sustainable and preserves its peculiarities.